THE EFFECT OF LEADERSHIP STYLE, WORK MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT THE REGIONAL SECRETARIAT (SETDA) OF SELAYAR ISLANDS REGENCY - Hasrul, Andi Arfan; Gani, Achmad; Hamzah, Muhammad Fadhil (Universitas Ichsan Sidenreng Rappang, 2025)
This research was conducted with the aim: (1) To analyze and explain the influence of leadership style on the performance of Regional Secretariat employees, (2) To analyze and explain the influence of work motivation on the performance of Regional Secretariat employees, and (3) To analyze and explain the influence of work discipline on the performance of Regional Secretariat employees. The research methods used in this study were descriptive analysis, instrument testing, multiple linear regression analysis, and hypothesis testing, with a sample size of 102 respondents. Based on the results of the multiple linear regression analysis, the study showed that (1) leadership style had a negative and insignificant effect on the performance of the Regional Secretariat of Selayar Islands Regency, (2) work motivation had a positive and significant effect on the performance of the Regional Secretariat of Selayar Islands Regency, and (3) work discipline had a positive and significant effect on the performance of the Regional Secretariat of Selayar Islands Regency.